PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 013 BAGAN HULU - Mardiana Mardiana; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a classroom action research (CAR) is done with the aim to improve learning outcomes IPS third grade students of SDN 013 Bagan Hulu. Research motivated by low yields social studies students is 65.00 by the number of students as many as 20 people. This study aims to improve learning outcomes IPS third grade students of SDN 013 Bagan Hulu to implement cooperative learning model type STAD. This study was conducted using research instrument in the form of observation sheets, and sheets achievement test. Based on the results of data analysis after the study was conducted by two cycles, it is known that the use of cooperative learning model STAD teacher can increase the activity of 79.17 in the first cycle of the meeting rose to 95.83 at the end of the cycle two. Furthermore kativitas students also increased from 66.67 in the first meeting of the cycle, increasing to 95.83 in cycle two. Increased activity was also accompanied by an increase in student learning outcomes IPS students. The average score of student learning outcomes 61.11 thereafter act as much as two cycles also increased to 94.44. Thus the implementation of cooperative learning model type of STD can improve learning outcomes by 0.54%. These research findings could prove the hypothesis of the research application STAD type of cooperative learning model can improve learning outcomes IPS class III SDN 013 Bagan Hulu. This means that the research hypothesis is accepted.Key Words ; STAD Cooperative, Learning Outcomes IPS